A Therapeutic Journey of Potential Drugs Against COVID-19 - Ali, Fayaz; Hussain, Shahid; Zhu, Yi Z. (Mini Reviews in Medicinal Chemistry, 2022)
Coronavirus disease (CoVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) scrambles the world by infecting millions of peoples all over the globe. It has caused tremendous morbidity, mortality and greatly impacted the lives and economy worldwide as an outcome of mandatory quarantines or isolations. Despite the worsening trends of COVID-19, no drugs are validated to have significant efficacy in the clinical treatment of COVID-19 patients in large-scale studies. Physicians and researchers throughout the world are working to understand the pathophysiology to expose the conceivable handling regimens and to determine the effective vaccines and/or therapeutic agents. Some of them re-purposed drugs for clinical trials which were primarily known to be effective against the RNA viruses including MERS-CoV and SARS-CoV-1. In the absence of a proven efficacy therapy, the current management use therapies based on antivirals, anti-inflammatory drugs, convalescent plasma, anti-parasitic agents in both oral and parenteral formulation, oxygen therapy, and heparin support. What is needed at this hour, however, is a definitive drug therapy or vaccine. Different countries are rushing to find this, and various trials are already underway. We aimed to summarize the potential therapeutic strategies as treatment options for COVID-19 that could be helpful to stop further spread of SARS-CoV-2 by affecting its structural components or modulation of immune response and discuss the leading drugs/vaccines, which are considered as potential agents for controlling this pandemic.
Keywords: MERS-CoV